Detection of Escherichia coli O157:H7 Strain from Diarrheal Children in Baghdad, Iraq Using Conventional and Molecular Methods - Thanaa R. Abdulrahman (Innovations in Biological Science Vol. 3, 2024)
Escherichia coli O157:H7 is a pathotype of Enterohemorrhagic Escherichia coli (EHEC) which is considered a public health problem bacteria-induced food-borne diarrheas, bloody diarrhea and hemolytic uremic syndrome that occurs at any age group. Three hundred stool samples were obtained from children with bloody diarrhea, from January 2015 to May 2015, their ages ranged from one month to five years who visited or were admitted as "out-patients" to Al-Eskan paediatrics hospital, Al-Kadhumia pediatric hospital or from a private clinic in Baghdad. Stool samples were cultured in tetrathionate broth, then inoculated in MacConkey agar for isolation and identification of lactose fermenter E. coli. Isolated E. coli is subcultured in modified Sorbitol MacConkey Agar (SMAC-CT) for selection of E. coli O157:H7. For confirmatory identification, the Latex agglutination test for E. coli O157:H7 was used and PCR for the detection of Shiga toxin 1 (vt1) gene. EHEC was found in 37 (12.33%) patients. The highest rate of 18 (48.64%) were in infants aged (3-12) months and 12 out of 37(32.43%) in the age group (13-24) months. 25 isolates were positive on Sorbitol MacConkey Agar with Cefixime and Tellurite (SMAC-CT). A commercial latex agglutination test revealed that E. coli: O157:H7 was found in 14(56%) out of 25 culture-positive cases while the other 11 (44%) isolates were E. coli O157: H- The results of PCR amplification of (vt1 gene) showed that 37 (12.33%) out of 300 stool samples were produced (130 pb) amplified band. All culture-positive samples (n=25) were also positive by PCR. These results concluded that this pathogen was considered one of the most important causes of gastrointestinal infection in children.